Processing of sustainable thermoplastic based biocomposites: A comprehensive review on performance enhancement. (20th September 2021) - Manral, Ankit; Kumar Bajpai, Pramendra; Ahmad, Furkan; Joshi, Rahul
Abstract: Depletion of petroleum products and the adverse effects of conventional material on environment has lead the awareness of natural fiber reinforced thermoplastic composites or green composites. Natural fiber reinforced thermoplastic composites have excellent properties such as high specific strength, lightweight, good acoustic insulation and exceptional sustainability. Aerospace, automobiles and household goods are some modern applications where the natural fiber reinforced green composites are being used. Green composites have replaced metals, alloys, wood and various nondegradable polymer composites in various applications. This study presents an exhaustive review on thermoplastic based natural fiber composites. Various factors such as fiber orientation, processing parameters, fiber surface modification etc. have been discussed in order to analyze how these factors affect the properties of natural fiber reinforced thermoplastic. A thorough analysis has been performed to categorize the factors influencing the properties of thermoplastic based composites. The present study also helps in identifying the optimum processing conditions to formulate and develop different types of natural fiber reinforced thermoplastic composites.